Ethanol and acetaldehyde metabolism in sheep : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biochemistry - Hendtlass, Jane (Massey University, 1973)
Ethanol and acetaldehyde metabolism in sheep has been studied in three different types of experiments:in purified enzyme systems, in liver homogenates and in the intact animals. Particular emphasis has been placed on the aldehyde oxidase enzyme from sheep liver, a molybdoflavoprotein with a broad specificity which includes aldehydes, quinines and N1-methyl nicotinamide. This thesis describes a method for preparing an enzyme solution in which sheep liver aldehyde oxidase constitutes 85% of the total protein present. Investigations of its physical and kinetic properties show that the sheep liver enzyme differs from the aldehyde oxidases previously prepared from pig and rabbit livers. In addition, an antibody to sheep liver aldehyde oxidase has been prepared from rabbit serum and has been shown to act as a specific, competitive inhibitor of the enzyme. This has been used to assess the contribution that aldehyde oxidase makes to acetaldehyde oxidation in sheep liver homogenates under several different conditions. The effects of steroids on ethanol and acetaldehyde metabolism has been investigated, special interest being taken in the effects of progesterone. Progesterone stimulates sheep liver aldehyde oxidase activity in vitro and inhibits sheep liver aldehyde dehydrogenase. Administration of progesterone to castrated sheep in vivo increased the rates of ethanol and acetaldehyde oxidation, and aldehyde oxidase has been identified as a factor in decreasing acetaldehyde concentrations in the homogenates of livers from these animals during the metabolism of exogenous ethanol. Low endogenous ethanol concentrations in peripheral venous blood of sheep are positively correlated with high progesterone levels in sheep due to its experimental administration, and to pregnancy and the oestrus cycle. Studies of the effects of disulphiram on ethanol and acetaldehyde metabolism have shown that the compound inhibits sheep liver aldehyde oxidase and aldehyde dehydrogenase enzymes in vitro, increases endogenous concentrations of acetaldehyde in peripheral venous blood, and causes acetaldehyde accumulation during ethanol metabolism in vivo. When diazepam is present together with disulphiram it provides protection from all but one of the effects shown by disulphiram alone. It does not alter the disulphiram inhibition of sheep liver aldehyde dehydrogenase. Amitryptyline is an inhibitor of both aldehyde oxidase and aldehyde dehydrogenase enzymes. It seems to increase the aldehyde oxidase response to disulphiram, and its in vivo administration causes acetaldehyde accumulation in peripheral blood during and in the absence of metabolism of exogenous ethanol. Investigations into the effects of ethanol on ethanol and acetaldehyde metabolism in sheep have shown that ethanol increases the activity of aldehyde oxidase in vitro and its chronic administration accelerates acetaldehyde oxidation in vivo. A supplementary study of the interrelationships between the relative concentrations of NADH and NAD+ , and ethanol and acetaldehyde metabolism shows that aldehyde oxidase participation in acetaldehyde oxidation is dependent on the NAD+ concentrations, and that acetaldehyde oxidation can account for much of the NADH accumulation that occurs during ethanol metabolism in vivo. Acetaldehyde oxidation during ethanol metabolism in sheep can be diverted through the aldehyde oxidase catalyzed pathway, avoiding dependence on the NAD+ -linked aldehyde dehydrogenase enzyme. The results in this thesis have shown that aldehyde oxidase can catalyze up to two-thirds of acetaldehyde oxidation in sheep liver when NAD+ is limited, and that the pathway is dependent on the endocrine state and the pattern of ethanol consumption of the animal
Keywords: Ethanol; Acetaldehyde; Alcohol in the body; Ethanol metabolism; Sheep liver